2021
DOI: 10.1002/rcs.2229
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of temporal bone structures from clinical conventional CT using a CNN approach

Abstract: Background Automatic segmentation of temporal bone structures from patients' conventional computed tomography (CT) data plays an important role in the image‐guided cochlear implant surgery. Existing convolutional neural network approaches have difficulties in segmenting such small tubular structures. Methods We propose a light‐weight three‐dimensional convolutional neural network referred to as W‐Net to achieve multiobjective segmentation of temporal bone structures including the cochlear labyrinth, ossicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…The proposed network model (W-Net) was described in detail in a previous study [ 30 ]. The W-net architecture in this study has no changes from the previously reported study [ 30 ]. Figure 1 shows the architecture of W-net.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed network model (W-Net) was described in detail in a previous study [ 30 ]. The W-net architecture in this study has no changes from the previously reported study [ 30 ]. Figure 1 shows the architecture of W-net.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study used data enhancement technology and 30 temporal bone CT volumes (15 left, 15 right) to develop the neural network model, which allowed the architecture to locate and render important structures on the left or right sides of the temporal bone CT [ 30 ]. We have used 24 volumes (12 left, 12 right) and 6 volumes (3 left, 3 right) as the training and validation set respectively, and trained the W-net network through five fold cross-validation [ 30 ]. It should be noted that the test set in this study were not included the training and validation data set in the previous study [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former approaches are mostly based on cochlear shape fitting based on template image registration (Baker and Barnes, 2005), parametric shape model (Baker, 2008). The supervised methods are based on statistical deformation models (Ruiz Pujadas et al, 2018) and deep learning (Lv et al, 2021;Raabid et al, 2021;Heutink et al, 2020).…”
Section: Comparison With the State-of-the-artmentioning
confidence: 99%
“…Deep Learning) is an effective way to perform image segmentation or processing in many cases. Specifically, in inner ear CT imaging analysis, many works achieved impressive results (Lv et al, 2021;Raabid et al, 2021;Heutink et al, 2020;Wang et al, 2019;Li et al, 2021;Alshazly et al, 2019;Zhang et al, 2019;Wang et al, 2020b). However, supervised learning methods have also many limitations.…”
Section: Introductionmentioning
confidence: 99%